How can we develop value chain programs that address climate risks? - Vermeulen, Sonja J.; Dinesh, Dhanush; Läderach, Peter R.D.; Mwongera, Caroline (2016)
The “How To Do Note: Climate change risk assessments in value chain projects” provides guidance for the design and development of climate-smart value chains. A number of tools and resources are available to support decision makers at various stages in value chain development. Mainstreaming climate risk management approaches in different stages of value chain development helps increase resilience of ￼￼smallholder farmers. The IFAD-CCAFS learning alliance generates and shares knowledge to support IFAD’s programming needs.